Fracture evaluation of energy components with local brittle zones - Praunseis, Zdravko (JET on-line, 2013)
The fracture toughness in the testing of multi-pass welds and heat-affected zones is remarkably sensitive to the microstructures in the vicinity of the crack tip of test specimen. Therefore, the introduction of the pre-crack to the weld and heat-affected zone specimen should be done most carefully. However, since there is an uncertainty of the crack tip position in fatigue precracking, it becomes common to section near the fatigue pre-crack front after testing is complete, and to examine the cross section in order to identify the position in weld and heataffected zone microstructures, the so-called local brittle zones. Concerning this sectioning technique, the precise experimental procedure is specified in this article.
Keywords: električna merjenja; elektrodinamika; energy components; fracture; izguba energije; prenos električne energije; sectioning technique brittle zones; zvari